2018
DOI: 10.3897/natureconservation.29.28943
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of mammals to land-use changes in Colombia’s post-conflict era

Abstract: Colombia, one of the most biodiverse countries in the world, is entering a peaceful period after more than fifty years of armed conflict. Due to land use changes resulting from this new situation, negative effects on biodiversity, including mammals are expected. We think that mammal populations will be more sensitive in municipalities where activities related to post-conflict will be carried out. In that order, we aim to: 1) identify which mammal species would be more sensitive and 2) identify the critical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…At the regional level, the economic, social, political, and cultural context can have different influences on the matrix. For example, post-conflict areas can modify the land uses and make some areas within biodiversity hotspots more sensitive for primates [125]. For species with broad geographic range distributed in more than one sub-region (e.g., Ateles belzebuth, present in the Amazon and Orinoco; Alouatta belzebul, in the Amazon and Atlantic Forest; and Alouatta palliata in Mesoamerica and Tumbes-Chocó-Magdalena) [126], we need to consider that deforestation rates are different among countries and forest types, and the amount of remaining natural habitat changes from one region to another [127,128].…”
Section: Discussionmentioning
confidence: 99%
“…At the regional level, the economic, social, political, and cultural context can have different influences on the matrix. For example, post-conflict areas can modify the land uses and make some areas within biodiversity hotspots more sensitive for primates [125]. For species with broad geographic range distributed in more than one sub-region (e.g., Ateles belzebuth, present in the Amazon and Orinoco; Alouatta belzebul, in the Amazon and Atlantic Forest; and Alouatta palliata in Mesoamerica and Tumbes-Chocó-Magdalena) [126], we need to consider that deforestation rates are different among countries and forest types, and the amount of remaining natural habitat changes from one region to another [127,128].…”
Section: Discussionmentioning
confidence: 99%
“…While habitat fragmentation and loss are common outcomes of perturbation, those that result in the curtailment of human activity can create de facto wildlife refuges, at least during the course of the perturbation (Annecke & Masubelele, 2016;Calle-Rendon et al, 2018;Coates, 2014;Constantinou et al, 2020;Conteh et al, 2017;Lawrence et al, 2015;Lindenmayer et al, 2016;Lindsell et al, 2011). Gains for conservation through de facto protection or F I G U R E 1 A conservation issue highlighted or driven by the COVID-19 pandemic, by case study site.…”
Section: Habitat Degradation and Fragmentationmentioning
confidence: 99%
“…However, in locations where enforcement capacity was reduced or communities were driven to unsustainably harvest resources due to a loss of livelihood opportunities or declines in trade, habitat integrity was compromised (Lindsey et al, 2020, Schwartz et al, 2020; CS2, Table 1). land abandonment may, however, be negated by tactical habitat destruction or settlement of populations in highly diverse habitats elsewhere (Calle-Rendon et al, 2018;Yong Sung et al, 2019). Long-term refuges have also been created from changing political, economic and technical fortunes (Agyeman & Ogneva-Himmelberger, 2009;Bragina et al, 2015;Hostert et al, 2011).…”
Section: Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Macroecological methods also can be used to examine potential relations between climate and violence among humans, which can have cascading negative or positive effects on species and ecosystems (e.g., Calle‐Rendon, Moreno, & Hilário, ; Daskin & Pringle, ; Francis, ; Lawrence, Stemberger, Zolderdo, Struthers, & Cooke, ). The first synthesis of literature on climate‐driven conflicts concluded that substantial deviations from long‐term average precipitation and temperature were associated with increases in the frequency of violence and conflict between individuals and populations (Hsiang, Burke, & Miguel, ).…”
Section: Macroecology and Social Inequities Related To Climate Changementioning
confidence: 99%